ADOLESCÊNCIA, ESCOLA DOMINICAL E EDUCAÇÃO: PERSPECTIVAS DE UM NOVO PROCESSO - Freitas, Jorge Wagner de Campos (2006)
The objective at this study is to identify some factors that have contributed for the evasion of adolescents of the Sunday School. Is study limits its scope to the Methodist Church in cities of the interior of the State of São Paulo. To understand the current condition of adolescence is a requisite to develop actions in order to make it able to the practice of faith. The first chapter focuses the adolescence development. Since the beginning of the Industrial Revolution, researchers, medical doctors, psychologists, educators among others have done research or this phase of life. Chapter two an analysis of the Sunday School. The goal of this chapter to understand its origins, its relationship with the adolescence its structure and functioning; since, it is one of the best spaces for adolescent formation. A the adolescent needs an educative model that helps his her development, and the Sunday School could be the educative agency to provide an appropriate education to the current time. The third chapter deepens the general concept of education and specifically the Christian education distinguishing them from education. The necessary model of education for the development of the adolescent must be that one the one that helps his her to elaborate its own development in a continuous practice of elaboration and rework of its education, allowing experiences of life in a Christian perspective. Finally, chapter four analyzes the result of the field research, the adolescent opinion on the Sunday School and from this understanding to identify the factors that contribute for the evasion.